cos x + 1 sin x + 2
Find the minimum value of the above expression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Typo: ( tan 2 x + 2 1 ) 2 + 4 3
( f ( x ) ) min = 4 3 when tan 2 x = − 2 1
Log in to reply
Corrected..
Log in to reply
There are two typos...
Let t = tan 2 x , then ⎩ ⎪ ⎨ ⎪ ⎧ sin x = 1 + t 2 2 t cos x = 1 + t 2 1 − t 2
Now, we have:
cos x + 1 sin x + 2 ⟹ cos x + 1 sin x + 2 = 1 + t 2 1 − t 2 + 1 1 + t 2 2 t + 2 = 1 − t 2 + 1 + t 2 2 t + 2 + 2 t 2 = t 2 + t + 1 = ( t + 2 1 ) 2 + 4 3 Since ( t + 2 1 ) 2 ≥ 0 ≥ 4 3 = 0 . 7 5 Minimum occurs when tan 2 x = − 2 1
If you differntiate the above function w.r.t. x then you eill get two solution from f'(x) which are cosx=-1 or cosx=3/5.
it can be seen that cosx!=-1 so putting cosx=3/5 we get minimum value 7/4
Log in to reply
You are right when minimum occurs tan 2 x = − 2 1 , ⟹ cos x = 5 3 and sin x = − 5 4 , ⟹ cos x + 1 sin x + 2 = 5 3 + 1 − 5 4 + 2 = 4 3 . You may have used sin x = 5 4 .
Log in to reply
Yes you are true.
I should take the minimum value
Thanks for explanation
Calculus method:
Let f ( x ) = cos x + 1 sin x + 2
For the expression to be valid, we know that cos x + 1 = 0 ⟹ cos x = − 1
Now, at minimum points, we know that f ′ ( x ) = 0
f ′ ( x ) = ( cos x + 1 ) 2 ( cos x + 1 ) ( cos x ) − ( sin x + 2 ) ( − sin x ) = ( cos x + 1 ) 2 cos 2 x + cos x + sin 2 x + 2 sin x = ( cos x + 1 ) 2 1 + cos x + 2 sin x
f ′ ( x ) = 0 ( cos x + 1 ) 2 1 + cos x + 2 sin x = 0 1 + cos x + 2 sin x = 0 1 + cos x = − 2 sin x 1 + cos x = − 2 1 − cos 2 x ( 1 + cos x ) 2 = ( − 2 1 − cos 2 x ) 2 1 + 2 cos x + cos 2 x = 4 ( 1 − cos 2 x ) 1 + 2 cos x + cos 2 x − 4 + 4 cos 2 x = 0 5 cos 2 x + 2 cos x − 3 = 0 ( 5 cos x − 3 ) ( cos x + 1 ) = 0 cos x = 5 3 , cos x = − 1
Now, we know that the second factor will result in f ( x ) being undefined, so we ignore it. This means that
cos x = 5 3 ⟹ sin x = − 2 1 + 5 3 = − 5 4
Therefore, the minimum value of the expression is 5 3 + 1 − 5 4 + 2 = 5 8 5 6 = 4 3 = 0 . 7 5
Note: The minimum value occurs at x = ( 3 0 6 . 8 7 + 3 6 0 n ) ∘ , where n is an integer
Bonus: My solution is actually incomplete. Prove that the point I found is a minimum point. If you used the second derivative test, you should get f ′ ′ ( x ) = 3 2 5 > 0
Very good solution. .
Let a = sin x + 1 , b = cos x + 1 . Then a and b satisfy ( a − 1 ) 2 + ( b − 1 ) 2 = 1 . We look to minimize b a + 1 = k . Through manipulation, we note that a − 1 = b k − 2 . We have ( a − 1 ) 2 + ( b − 1 ) 2 = ( b k − 2 ) 2 + ( b − 1 ) 2 = b 2 ( k 2 + 1 ) − b ( 4 k + 2 ) + 5 = 1 .
We know that the polynomial b 2 ( k 2 + 1 ) − b ( 4 k + 2 ) + 4 = 0 has real roots, therefore its discriminant is greater than or equal to zero. ( − ( 4 k + 2 ) ) 2 − 4 ( k 2 + 1 ) ( 4 ) ≥ 0 1 6 k − 1 2 ≥ 0 k ≥ 4 3 = 0 . 7 5
Interesting Fact: This problem can share a similar solution to this one.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Sum and Difference Trigonometric Formulas - Problem Solving
f ( x ) = cos x + 1 sin x + 2
Use sin x = 2 sin 2 x cos 2 x , 1 + cos x = 2 cos 2 2 x .
f ( x ) = = = = 2 cos 2 2 x 2 sin 2 x cos 2 x + 2 cos 2 2 x 2 tan 2 x + 1 + tan 2 2 x sec 2 2 x tan 2 2 x + tan 2 x + 1 ( tan 2 x + 2 1 ) 2 + 4 3
Since square of a real quantity is always non negative.
( f ( x ) ) min = 4 3 when tan 2 x = 2 − 1